Monoamine oxidase inhibition in cigarette smokers: From preclinical studies to tobacco product regulation - Sved, Alan F.; Weeks, Jillian J.; Grace, Anthony A.; Smith, Tracy T.; Donny, Eric C. (Frontiers in Neuroscience, 2022)
Monoamine oxidase (MAO) activity is reduced in cigarette smokers and this may promote the reinforcing actions of nicotine, thereby enhancing the addictive properties of cigarettes. At present, it is unclear how cigarette smoking leads to MAO inhibition, but preclinical studies in rodents show that MAO inhibition increases nicotine self-administration, especially at low doses of nicotine. This effect of MAO inhibition develops slowly, likely due to plasticity of brain monoamine systems; studies relying on acute MAO inhibition are unlikely to replicate what happens with smoking. Given that MAO inhibition may reduce the threshold level at which nicotine becomes addictive, it is important to consider this in the context of very low nicotine content (VLNC) cigarettes and potential tobacco product regulation. It is also important to consider how this interaction between MAO inhibition and the reinforcing actions of nicotine may be modified in populations that are particularly vulnerable to nicotine dependence. In the context of these issues, we show that the MAO-inhibiting action of cigarette smoke extract is similar in VLNC cigarettes and cigarettes with a standard nicotine content. In addition, we present evidence that in a rodent model of schizophrenia the effect of MAO inhibition to enhance nicotine self-administration is absent, and speculate how this may relate to brain serotonin systems. These issues are relevant to the MAO-inhibiting effect of cigarette smoking and its implications to tobacco product regulation.